Immunotherapy for House Dust Mite Sensitivity: Where are the Knowledge Gaps? - Biagtan, Mark (Curr Allergy Asthma Rep, 2014)
House dust mites (HDM) are found in the environments where human habitation exists. Their density is dependent on environmental relative humidity; therefore higher populations are present in areas of the world with higher humidity levels e.g. coastal areas, tropics. To date 24 HDM allergens have been identified. Many of these represent digestive enzymes since HDM feces are the major source of allergen exposure. IgE- medicated sensitization to HDM allergens is an important factor in the pathogenesis of allergic diseases since it is the most common aeroallergen detected by skin testing or in vitro IgE assays. Sensitization to HDM allergens often occurs early in life and appears to play an important role in the progression from allergic rhinitis to asthma (the so-called “Allergic March”) in children. HDM sensitization is also associated with asthma across all age groups. Efforts to control environmental exposure to HDM allergens have often proven to be unsuccessful. While medications can improve symptoms, only immunotherapy currently provides disease modifying effects in allergic rhinitis and asthma. Several systemic reviews and meta-analysis indicate that both SCIT and SLIT are effective in the treatment of allergic rhinitis and asthma for HDM sensitivity. In this report we review recent studies and the evidence for the use of HDM SCIT and SLIT. Fundamental gaps in knowledge are identified which could lead to improved approaches to HDM allergy.